Green nanoparticle formation toward wound healing, and its application in drug delivery approaches - Pooja Sharma; Navneet; Aparna Kaushal (Elsevier, 2022)
Wound infection has become a matter of concern for public health, so wound care centers are focusing on the development of unique and novel approaches. As a result, the development of these approaches is having a great clinical impact. Nanotechnology is a very effective technology for different remedies systems based on small nanomaterials in which the approach of green synthesis of nanoparticles is becoming more suitable for different activities. Researchers have developed a suitable approach for metal nanoparticles formation. Surprisingly, the concept of green formation is receiving much consideration right now. In green synthesis, nanoparticles have played a significant role due to their higher reactivity and stability from different sources i.e. bacteria, fungus, algae and plants. It exhibited that different sources i.e. bacteria, fungus, algae and plants, can reduce metal ions into metal nanoparticles by NADPH-dependent reductase enzyme. Nanoparticles interact with different biomolecules including lysosomes, ribosomes, and DNA. However, it affects their oxidative stress, cell permeability, protein synthesis, and gene expression of different pathogens. Thus, bacteria have difficult situations of hindrance against them. In this current review, we are focusing on the different compounds of nanoparticles against wound healing and their applications like antioxidant, antibacterial, and antifungal activities. This review provides information regarding nanoparticles from different resources against wound infections.